SISTEM INFORMASI PENJUALAN DAN PEMBELIAN PADA PT GANESA MITRA EDUTAMA BERBASIS DESKTOP - Agustina, Nisa; Rum, Avid Inang (Jurnal Mahasiswa Terapan; Vol 1 No 1 (2024): Jurnal Mahasiswa Terapan, 2024)
Sales and purchase information system is an information system that provides information about sales and purchases at a company. The purpose of the study was to analyze, design, implement and test the sales and purchase information system at PT Ganesa Mitra Edutama. This system is designed to overcome the problem of difficulty in compiling sales and purchase reports, managing old sales and purchase data, human error or data input errors, difficulty in searching data, and the risk of miscalculation in recording transactions. The data collection techniques used are interviews, observations, literature studies. The method used for data analysis is the PIECES (Performance, Information, Economy, Control, Efficiency, Service) analysis method. The system development method that the author uses in this research is Waterfall. In the research the author used a black box to test the system. The results of implementation and testing are the process of recording sales and purchases carried out automatically by the system, so that data will be stored safely and does not require a long time in managing sales and purchase data. the system will calculate sales and purchase data automatically to avoid calculation errors. The search feature contained in the sales and purchase application also makes it easy to search for the desired data. There are access rights for system security.